Sir Harry Lauder and the Scots Diaspora: Cementing Identity through Stage and Screen. Issue 3 (2nd September 2019) - Ritchie, John
Abstract : Once the most famous Scotsman in the world, Sir Harry Lauder never managed to become a star of the silver screen. Despite this, his name and image still immediately signify Scottishness because of his successful and lengthy stage career. This article examines Lauder and the manner in which he helped to cement this specific identity for Scotsmen across the English-speaking world, tracing his forays from stage to screen in both silent and early sound cinema.